NOUN PHRASES IN TOURISM SLOGANS OF ASIAN COUNTRIES - Zenabela Amalia Putri (LINGUA LITERA : journal of english linguistics and literature, 2018)
The aims of the research are to find out the structure of noun phrases and to analyze the textual functions of noun phrases in tourism slogans of Asian Countries. The writer was interested in noun phrase because it is used to promote the product. To promote the product, advertising language uses slogan. Furthermore, the method and the technique used in this thesis were qualitative method and referential technique. Meanwhile, for the process of analyzing data the distributional method was used. The writer applied the theory of Robert (2006), Leech and Svantik (1975), Jacobs and Resebaum (1968) to find out the structures of noun phrase, and theory of Matheson (2005) to find out the textual functions. Based on the analysis there were several textual functions found. The first was to emphasize the noun phrase in order to attract people to visit the country. The second was to make people think, feel and believe in the situation based on the pictures of the slogans. Thus, the writer hopes the readers gain more knowledge and understanding about noun phrases especially noun phrasesin tourism slogans.